Long‐term renal functional outcomes following ureteroureterostomy performed during multi‐organ resection for non‐urothelial cancers. Issue 5 (5th May 2021) - Pisters, Phillip W.; Ranasinghe, Weranja; Wei, Wei; Wood, Christopher G.; Matin, Surena F.; Ward, John F.; Pisters, Louis L.
Abstract: Objectives: To evaluate the long‐term renal function outcomes after ureteroureterostomy (UU) in patients undergoing multi‐organ resection for non‐urothelial cancers. The secondary aim was to examine the length of ureteric defect that can be successfully bridged with UU. Patients and methods: We retrospectively reviewed the charts of patients who underwent UU between 1995 and 2012 at our institution. Renal imaging studies performed before and after UU were used to determine whether hydronephrosis was present. Renal function was assessed by comparing estimated glomerular filtration rate (eGFR) before and at the last follow‐up after UU. Results: Nineteen patients underwent UU during multi‐organ resection for non‐urothelial cancers. Median follow‐up time was 62 months. Overall, UU had a high success rate, with one patient (5.2%) developing progressive hydronephrosis with a >20% drop in eGFR from baseline due to UU failure. Four additional patients developed progressive hydronephrosis due to cancer recurrence involving the UU. There were no statistically significant differences between pre‐ and post‐UU eGFR in these patient cohort. All patients with a ureteric defect of ≤5 cm underwent successful reconstruction. Conclusions: UU maintains long‐term renal function in the majority of patients undergoing multi‐organ resection for non‐urothelial cancers and can be successfully utilized if the resected ureteric length is ≤5 cm.